“The Assistance of Science and Capital”: The Role of Technology in Establishing B.C.’s Hard Rock Mining Industry, 1876-1906 - Mouat, Jeremy (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1992)
ABSTRACTThis article examines the role of technology and applied science in British Columbia's hard rock mining industry. It focuses on a transitional period, from the decline following the gold rushes of the mid century through to the emergence in 1906 of Cominco, a vertically-integrated mining and smelting complex typical of the large mining companies of the twentieth century. Although many contemporary observers held a naive faith in the possibilities of science and technology, the article argues that the transition to "modern mining" was more difficult and more complex than they had anticipated and its outcome a good deal more ambivalent.